The use of system dynamics for energy and environmental education - Strapasson, Alexandre (2022)
The use of system dynamics as a learning tool for developing sustainable energy strategies and environmental education has advanced in recent years with the availability of new modelling software and webtools. Among the existing models, we highlight the online 2050 Calculators, which aim at simulating scenarios for greenhouse gas emissions, energy planning, sustainable land use, and food consumption. The objective of this study is to assess the available calculators and their contribution to an interdisciplinary education via systems thinking. We carried out a review of the existing models worldwide and ran some of the tools with students from three diferent postgraduate programmes at master’s level at Imperial College London (United Kingdom) and IFP School (France), whilst also assessing their individual views afterwards. The assessments were conducted once a year during three subsequent years: 2019, 2020, and 2021. The results are discussed under the epistemology of critical pedagogy, showing that the use of webtools, such as the 2050 Calculators, can signifcantly contribute to the students’ environmental awareness and political engagement, providing important lessons about the use of system dynamics for policy and science education.